2012
DOI: 10.4103/0974-7761.115151
|View full text |Cite
|
Sign up to set email alerts
|

Relating dental caries experience with body mass index among Nigerian primary school children: A cross-sectional survey

Abstract: Objective:To determine the dental caries experience and body mass index (BMI) of primary school children from both public and private schools in Ugbowo, Benin City. Materials and Methods: Primary school children from conveniently selected private and public schools were examined for dental caries and also underwent height and weight measurement for their BMI calculation during the Association of Resident Doctors, University of Benin Teaching Hospital School Health program in December 2010, using the WHO criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Prevalence and pattern of dental caries among a sample of Nigerian public primary school children Adeniyi [31] Combined age groups Prevalence of dental caries: national pilot study comparing the severity of decay (CAO) vs ICDAS index in Senegal Aidara [32] Sociobehavioural risk factors of dental caries among selected adolescents in Ibadan, Nigeria Ajayi [33] Assessment of dental caries status among school children aged 9-12 years of Sebha city-Libya by using of dft/ DMFT & SiC indices Arrish [34] Caries experience and caries predictors-a study of Tanzanian children consuming drinking water with different fluoride concentrations Awadia [35] Relating dental caries experience with body mass index among Nigerian primary school children: A cross-sectional survey Azodo [36] Fluorosis, caries and oral hygiene in schoolchildren on the Ombili foundation in Namibia Berndt [37] Severity of dental caries among 12-year-old Sudanese children with different fluoride exposure Birkeland [38] Wrong year of publication Prevalence of oral conditions and associated factors among schoolchildren in Accra, Ghana: a crosssectional study…”
Section: Diagnostic Criteria Is the Methods Used To Evaluate Dental C...mentioning
confidence: 99%
“…Prevalence and pattern of dental caries among a sample of Nigerian public primary school children Adeniyi [31] Combined age groups Prevalence of dental caries: national pilot study comparing the severity of decay (CAO) vs ICDAS index in Senegal Aidara [32] Sociobehavioural risk factors of dental caries among selected adolescents in Ibadan, Nigeria Ajayi [33] Assessment of dental caries status among school children aged 9-12 years of Sebha city-Libya by using of dft/ DMFT & SiC indices Arrish [34] Caries experience and caries predictors-a study of Tanzanian children consuming drinking water with different fluoride concentrations Awadia [35] Relating dental caries experience with body mass index among Nigerian primary school children: A cross-sectional survey Azodo [36] Fluorosis, caries and oral hygiene in schoolchildren on the Ombili foundation in Namibia Berndt [37] Severity of dental caries among 12-year-old Sudanese children with different fluoride exposure Birkeland [38] Wrong year of publication Prevalence of oral conditions and associated factors among schoolchildren in Accra, Ghana: a crosssectional study…”
Section: Diagnostic Criteria Is the Methods Used To Evaluate Dental C...mentioning
confidence: 99%
“…The association between ECC and malnutrition is however, not clear. Although a few studies have found an association between ECC, body mass index (BMI) [1113] and growth failure [1418], others have found no associations [6, 1921]. Also, while large population-based studies found no association between BMI and ECC [19, 2224], a longitudinal study indicated that malnutrition causes ECC [25], ECC causes stunting, and underweights have more ECC [26], ECC and obesity are both risk factors for type 2 diabetes [27].…”
Section: Introductionmentioning
confidence: 99%
“…The studies on the association between malnutrition and caries in Nigeria were conducted in children older than 5 years [11, 40]. These studies were school-based and found no association between BMI and caries.…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of analysis, of caries experience, the participants with DMFT 0 were categorized as having no dental caries while those with DMFT of 1 or more were categorized as having dental caries. [15] An accepted method to evaluate an individual's body weight relative to population norms was determined by calculating BMI by dividing weight in kilograms divided by the square of height in meters. [16,17] Moreover, the WHO had stated BMI provides the most useful population-level measure of overweight and obesity as it is the same for both sexes and all ages of adults; [3] hence, BMI was used to measure obesity in the present study.…”
Section: Methodsmentioning
confidence: 99%